Comparison of passive and active motion: effect of myokine irisin on cartilage in knee osteoarthritis rats - Duan, Zhengjiao; Gao, Hongpan; Xiao, Xue; He, BenXiang (Frontiers in Physiology, 2025)
IntroductionKnee osteoarthritis (KOA) severely impacts knee joint health. Irisin, a myokine secreted during muscle contraction, varies with different exercise. This study investigates the chondroprotective effects of irisin induced by active and passive motion in a rat model of KOA.MethodsThe rats were randomly allocated into control (CG), model (OAG), passive motion (PAG), and active motion groups (AAG). KOA was induced by intra-articular injections of monosodium iodoacetate (MIA) in all groups except CG. The PAG and AAG group underwent 4 weeks of treadmill exercise or quadriceps femoris muscle electroacupuncture. Changes in irisin, chondrocyte metabolic markers, and inflammatory factors were evaluated using ELISA, histology, immunohistochemistry, and qRT-PCR. Pearson correlation analysis was performed to assess the relationship between irisin and inflammatory factors.ResultsOne-week post-modeling, the OAG group showed the lowest hindlimb grip strength and quadriceps weight, chondrocyte number, collagen II expression and irisin levels, while displaying the highest levels of matrix-degrading enzymes (MMP-13, MMP-9, ADAMTS-5) and inflammatory factors (IL-6, TNF-α, IL-1β, IL-18). However, after 4 weeks of intervention, both the PAG and AAG groups reversed these trends. The PAG group exhibited greater improvements in hindlimb grip strength and quadriceps weight compared to the AAG group. HE staining, toluidine blue and safranin O showed smoother cartilage surfaces, increased cartilage thickness and stronger safranin O staining in PAG and AAG groups compared to OAG. Collagen II protein expression was upregulated (P < 0.001), while MMP–13 was downregulated (P < 0.001), and the mRNA levels of MMP-9 and ADAMTS-5 were downregulated (P < 0.001). Moreover, inflammatory factors were lower in PAG than in AAG. Irisin expression was highest in the PAG group, followed by AAG, CG, and OAG group, in serum, synovial fluid and cartilage. Irisin levels were negatively correlated with IL-6, TNF-α, IL-1β, and IL-18.ConclusionBoth active and passive motion inhibited cartilage degeneration in KOA rats, with passive exercise showing superior effects on muscle strength, irisin secretion, and downregulation of inflammatory cytokines. The chondroprotective and anti-inflammatory effects were positively correlated with increased irisin expression.